CAMPELLO, Eliane T. A. O Künstlerroman de autoria feminina: a poética da artista em Atwood, Tyler, Piñon e Valenzuela. - Bailey, Cristina Ferreira-Pinto (Revista Estudos Feministas, 2005)
CAMPELLO, Eliane T. A. O Künstlerroman de autoria feminina: a poética da artista em Atwood, Tyler, Piñon e Valenzuela.